Mapping Jewish identities : migratory histories and the transnational re-framing of 'Ashkenazi BRCA mutations' in the UK and Brazil - Mozersky, Jessica (Routledge, 2014)
This chapter builds on studies at the emerging intersection of medical and population genetics by examining the different ways in which narratives of ancestry and migratory history have been, and are becoming, linked to mutations in the high-risk breast cancer genes BRCA1 and BRCA2. In particular, it examines how these historical narratives - initially associated with Ashkenazi Jewish communities and subsequently with diverse regions and populations - have become variously incorporated into different domains of transnational medical research and clinical practices. Drawing on ethnographic research in the UK and Brazil, this article compares the ways in which health professionals (research scientists and clinicians) communicate, understand and situate narratives of history and migration associated with Ashkenazi Jewish populations and the varied consequences this has for the way patients engage with and incorporate this knowledge into understandings of risk and identity. In this way, we aim to highlight several contrasting dynamics surrounding the transnational re-framing of 'Ashkenazi BRCA mutations'